2012
DOI: 10.1186/1465-9921-13-88
|View full text |Cite
|
Sign up to set email alerts
|

Lipoteichoic acid induces surfactant protein-A biosynthesis in human alveolar type II epithelial cells through activating the MEK1/2-ERK1/2-NF-κB pathway

Abstract: BackgroundLipoteichoic acid (LTA), a gram-positive bacterial outer membrane component, can cause septic shock. Our previous studies showed that the gram-negative endotoxin, lipopolysaccharide (LPS), could induce surfactant protein-A (SP-A) production in human alveolar epithelial (A549) cells.ObjectivesIn this study, we further evaluated the effect of LTA on SP-A biosynthesis and its possible signal-transducing mechanisms.MethodsA549 cells were exposed to LTA. Levels of SP-A, nuclear factor (NF)-κB, extracellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 34 publications
(57 reference statements)
1
9
1
Order By: Relevance
“…We have demonstrated that rhHsp70, LPS or LTA alone and in combinations did not influence metabolic activity of NCI‐H292 cells. In agreement with our results, it was reported that eHsp70, LPS and LTA do not exert toxic effects on various cell types . For instance, Hsp70 treatment did not alter cell viability of A549 human lung cancer cells, HL‐60 promyelocytic leukaemia cells and neutrophils .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We have demonstrated that rhHsp70, LPS or LTA alone and in combinations did not influence metabolic activity of NCI‐H292 cells. In agreement with our results, it was reported that eHsp70, LPS and LTA do not exert toxic effects on various cell types . For instance, Hsp70 treatment did not alter cell viability of A549 human lung cancer cells, HL‐60 promyelocytic leukaemia cells and neutrophils .…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with our results, it was reported that eHsp70, LPS and LTA do not exert toxic effects on various cell types. [22][23][24][25] For instance, Hsp70 treatment did not alter cell viability of A549 human lung cancer cells, 14 HL-60 promyelocytic leukaemia cells 22 and neutrophils. 25 In addition, treatment of human bronchial epithelial cell line BEAS-2B with LPS did not affect cell viability 24 as well as treatment of human lung carcinoma type II epithelial cells A549 with LTA.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Analysis of various signaling pathways in the mutant mice points to a possible mechanism for the surfactant deficiency and consequently, offers other points of potential therapeutic intervention. Synthesis of surfactant proteins has been shown to be driven by a MEK1/2 –ERK1/2 pathway [ 46 , 47 ] and ERK downregulation attenuates expression of both surfactant proteins [ 15 , 48 ] and MMP9 [ 49 ]. The ERK pathway was downregulated in our mutant mice ( Fig 1C ) and correlates with the observed changes in pulmonary surfactant production.…”
Section: Discussionmentioning
confidence: 99%
“…aureus infection. A previous study reported that exposure to LTA increased Surfactant protein A (SP-A) expression in human alveolar type II epithelial cells through sequentially activating the MEK1-ERK1/2-NF-κB-dependent pathway [ 59 ]. S .…”
Section: Discussionmentioning
confidence: 99%